A Segmented Cell Measuring Technique for Current Distribution Measurements in Batteries, Exemplified by the Operando Investigation of a Zn-Air Battery. Issue 12 (20th December 2021) - Kube, Alexander; Meyer, Jens; Kopljar, Dennis; Wagner, Norbert; Friedrich, Kaspar Andreas
Abstract : A transimpedance amplifier circuit as well as an instrumental amplifier circuit were used to measure current densities of a zinc-air battery with an integrated segmented current collector foil. Error calculation showed that the transimpedance amplifier is superior to the used instrumental amplifier, but both methods provide valuable and consistent results. They both showed comparable results with operando insight into the current distribution of the battery. The knowledge about those distributions is essential to avoid fast degradation of battery materials and irreversible capacity loss due to heterogeneous dissolution of the anode during discharge. In this work we showed that oxygen starvation as well as gas flow rate leads to large current gradients. It was also demonstrated that heterogeneous current distributions on cathode side induces also a heterogenous dissolution behavior on the anode, resulting in irreversible capacity loss.